THE LEVEL OF MACRO NUTRIENT INTAKE AND NUTRITIONT STATUS OF LABOR IN SUN ISLAND HOTEL AND SPA KUTA - Ni Luh Bunita Shelayanti; Ni Made Yuni Gumala; Ketut Lilik Arwati (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2021)
Nutritional status is the end result of the balance between food intake the body (nutrient input) with the body's needs (nutrient output) of these nutrients. Macro nutrient is the largest component of the composition of the diet and serves to supply energy and essential nutrients. The purpose of this study was to determine the level of macro nutrient intake and nutritional status of workers at Sun Island Hotel and Spa Kuta. This study were observational with a cross sectional design. The total sample of this study was 32 samples. Nutritional status data is taken by measuring height and weighing the body. The level of energy consumption and macro nutrients is obtained by performing a 2 x 24 hour recall. As many as 17 samples (53.12%) with normal nutritional status, as many as 4 samples (12.5%) were obese nutritional status, and 11 samples (34.37%) were very fat nutritional status. The level of energy consumption deficit with normal nutritional status was 13 samples (76,47%), the level of consumption of protein deficits with normal nutritional status was 16 samples (94.12%), the level of fat deficit consumption with normal nutritional status was 9 samples (52,94%), and carbohydrate consumption deficits with normal nutritional status were 13 samples (76.47%).